2013
DOI: 10.1161/circresaha.111.256149
|View full text |Cite
|
Sign up to set email alerts
|

Steps Toward Safe Cell Therapy Using Induced Pluripotent Stem Cells

Abstract: Ever since pioneering reports introduced mouse 1 and humaninduced 2-4 pluripotent stem cells (iPSCs) to the scientific community and the populace at large, there has been an increasing interest in applications for their use in the fields of biomedical research. These include cell therapy in regenerative medicine and modeling of human disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
292
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 380 publications
(304 citation statements)
references
References 90 publications
1
292
0
6
Order By: Relevance
“…Recently, research on this problem has rapidly progressed, and many studies have proposed solutions [40], including establishment of iPS cells with transient gene expression instead of using retroviruses or lentiviruses [38,[41][42][43], by introducing proteins [44][45][46], by substituting some genes with drugs [44,46] and by using minicircle vectors that enable longer-term gene expression than plasmid vectors [47]. According to the results of our previous studies, transgene reactivation npg and incomplete reprograming are considered as the main causes of tumorigenesis, and we propose to use integration-free iPS cells reprogramed using episomal vectors in the future to overcome the first of these problems [40,48]. Furthermore, among our most important tasks before successful clinical application will be to induce Glis-1-transduced iPS cells, developed by Yamanaka et al [49], which are reprogramed more completely, this allowing them to differentiate reliably into NS/PCs, and to accurately evaluate the safety of this final product.…”
Section: Future Problems and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, research on this problem has rapidly progressed, and many studies have proposed solutions [40], including establishment of iPS cells with transient gene expression instead of using retroviruses or lentiviruses [38,[41][42][43], by introducing proteins [44][45][46], by substituting some genes with drugs [44,46] and by using minicircle vectors that enable longer-term gene expression than plasmid vectors [47]. According to the results of our previous studies, transgene reactivation npg and incomplete reprograming are considered as the main causes of tumorigenesis, and we propose to use integration-free iPS cells reprogramed using episomal vectors in the future to overcome the first of these problems [40,48]. Furthermore, among our most important tasks before successful clinical application will be to induce Glis-1-transduced iPS cells, developed by Yamanaka et al [49], which are reprogramed more completely, this allowing them to differentiate reliably into NS/PCs, and to accurately evaluate the safety of this final product.…”
Section: Future Problems and Perspectivementioning
confidence: 99%
“…Furthermore, among our most important tasks before successful clinical application will be to induce Glis-1-transduced iPS cells, developed by Yamanaka et al [49], which are reprogramed more completely, this allowing them to differentiate reliably into NS/PCs, and to accurately evaluate the safety of this final product. In addition to these improvements of the iPS cells, the safety issues must be validated through the intensive quality examination of iPS cell-derived NS/PCs in terms of genetic and epigenetic status, and their differentiation, proliferation and tumorigenicity In vivo, prior to the first human trials [40]. Finally, another important challenge before attempting clinical application pertains to the use of agents and cells derived from xenogeneic sources.…”
Section: Future Problems and Perspectivementioning
confidence: 99%
“…97 time, there are significant limitations to the use of iPSCs including slow propagation, concerns for incomplete reprogramming, immunogenicity and potential tumourigenesis. 98 Currently, there is a proposed human trial of iPSCs in Japan in which six patients with exudative age-related macular degeneration will have autologous iPSC-generated retinal pigment epithelial sheath transplantation (please see http://www. riken-ibri.jp/AMD/english/research/index.html).…”
Section: Dmd = Disease-modifying Drug; Ipsc = Induced Pluripotent Stementioning
confidence: 99%
“…Previous studies have demonstrated that NS/PC transplantation promotes functional recovery in spinal cord injury (SCI) animal models, prompting several investigators to proceed to clinical applications [4][5][6][7][8][9][10]. Some clinical trials responses between rodents and primates [12,13].…”
Section: Introductionmentioning
confidence: 99%